Virtual ankle-brachial index – can the immediate outcome of femorodistal bypass surgery be predicted? - Sekulić, Dragan B.; Tomić, Aleksandar B.; Dimić, Andreja; Mitrović, Aleksandar C.; Davdović, Lazar B.; Paunović, Dragana S.; Nikolić, Dalibor D.; Miladinović, Uroš M.; Sekulić, Igor M.; Rančić, Nemanja K.; Šarac, Momir M.; Marjanović, Ivan R.; et al. (Vojnosanitetski pregled, 2023)
Background/Aim. The best treatment for the occlusion of the largest artery in the thigh is a femorodistal (FD) bypass. Ankle-brachial index (ABI) and multidetector computed tomographic (MDCT) angiography are the gold standards for diagnosing peripheral arterial occlusive disease. The finite element analysis (FEA) method can help measure the quantity of blood flow and arterial pressure in the arteries in the leg. The aim of this study was to examine the possibility of using the FEA method in predicting the outcome of FD bypass surgery. Methods. The study involved 45 patients indicated for FD arterial reconstruction from December 1, 2021, to March 31, 2023. Each patient underwent pre- and postoperative MDCT angiography of the arteries of the lower extremities, on the basis of which, with the use of FEA, models were made for measuring ABI. All patients had their ABI measured preoperatively and postoperatively using the Doppler ultrasound and sphygmomanometer. Based on the findings of the preoperative MDCT angiography, postoperative virtual surgical models were created using the FEA method, on which ABI were also measured. The values of ABI were divided into five groups: ABI measured preoperatively (ABI pre-op), ABI measured postoperatively (ABI post-op), ABI measured on FEA models based on the MDCT findings [ABI (sim) pre-op], ABI sim post-op, and ABI measured on virtual surgery model [ABI sim post-op (virtual)]. The ABI of the models were statistically compared with preoperative and postoperative measurements done on patients. Results. The values based on the virtual ABI model did not show significant differences compared to the values obtained on patients and values obtained with the FEA method using MDCT angiography (p < 0.001). A strong statistically significant correlation was shown between the virtual ABI and the values obtained by the other two methods, measured on the postoperative MDCT angiography model and virtual postoperative model (p < 0.001). Conclusion. Virtual simulation based on the MDCT angiography parameters of peripheral blood vessels can be successfully used to predict the immediate outcome of the FD bypass surgery.